2020
DOI: 10.1101/2020.05.17.20104869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenic profile of SARS-CoV-2 spike in individuals recovered from COVID-19

Abstract: The rapid global spread of SARS-CoV-2 and resultant mortality and social disruption have highlighted the need to better understand coronavirus immunity to expedite vaccine development efforts. Multiple candidate vaccines, designed to elicit protective neutralising antibodies targeting the viral spike glycoprotein, are rapidly advancing to clinical trial. However, the immunogenic properties of the spike protein in humans are unresolved. To address this, we undertook an in-depth characterisation of humoral and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 48 publications
(72 reference statements)
15
57
0
Order By: Relevance
“…113 Neutralising ability correlated in particular with competition for the angiotensin converting enzyme -2 (ACE2) receptor. 70,72,106 Two studies demonstrated a lack of association with affinity, 73,106 although a moderate correlation with binding affinity was reported in one study. 107 Potently neutralising N specific antibodies were isolated in other studies, 73,109 and the potential for antibodies binding to protease cleavage sites as alternatives to RBD isolated from convalescent plasma has also been identified, 114 population.…”
Section: Correlation Of Neutralisation With Specific Antibodiesmentioning
confidence: 95%
See 1 more Smart Citation
“…113 Neutralising ability correlated in particular with competition for the angiotensin converting enzyme -2 (ACE2) receptor. 70,72,106 Two studies demonstrated a lack of association with affinity, 73,106 although a moderate correlation with binding affinity was reported in one study. 107 Potently neutralising N specific antibodies were isolated in other studies, 73,109 and the potential for antibodies binding to protease cleavage sites as alternatives to RBD isolated from convalescent plasma has also been identified, 114 population.…”
Section: Correlation Of Neutralisation With Specific Antibodiesmentioning
confidence: 95%
“…29,49,67,74,87,[99][100][101] Specifically, high quality studies found that neutralisation ability correlated positively with anti-S IgG 49,72,87,99 or anti-RBD IgG. 72,74,87,102 There was more limited evidence for correlation with anti-RBD IgM, including one high quality study, 51,84 and IgA. 93,99 A number of basic science studies also identified specific neutralising antibodies.…”
Section: Correlation Of Neutralisation With Specific Antibodiesmentioning
confidence: 99%
“…Unfortunately, no vaccines for any of the known human CoVs have been licensed (143,144), although several potential SARS-CoV and MERS-CoV vaccines have advanced into human clinical trials for years (117,145), suggesting the development of effective vaccines against human CoVs has always been challenging. However, it has been shown that both SARS-CoV and SARS-CoV-2 could readily induce neutralizing antibodies following natural infection or immunization (146)(147)(148)(149). Moreover, a growing number of neutralizing monoclonal antibodies targeting the SARS-CoV-2 S glycoprotein with high potency have been isolated from plenty of convalescent donors (33) as well as humanized mice (136,141), some of which have been shown to afford protection against SARS-CoV-2 challenge in animal models.…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
“…The development of antibodies to SARS-CoV-2 has been assessed in COVID-19 patients at different disease stages and severities. Specific IgA, IgM, IgG, or total antibodies to SARS-CoV-2 antigens, including full length S protein, RBD, E, and N proteins, were assessed for binding activities in peripheral blood of a total of 4,261 patients (Table 1) Juno et al, 2020;Li et al, 2020a;Long et al, 2020a;Lou et al, 2020;Lynch et al, 2020;Ni et al, 2020;Prevost et al, 2020;Ren et al, 2020;To et al, 2020b;Wajnberg et al, 2020;Wang et al, 2020e;Yu et al, 2020a;Zhang et al, 2020c;Zhao et al, 2020). Additional studies were also analyzed and presented in a systemic review (Deeks et al, 2020).…”
Section: Humoral Responses To Sars-cov-2 Infection In Covid-19 Patientsmentioning
confidence: 99%